2020
DOI: 10.1155/2020/5432651
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms Triggered by the Cotreatment of Resveratrol and Doxorubicin in Breast Cancer: A Translational In Vitro–In Silico Model

Abstract: Doxorubicin (Doxo) is the most effective chemotherapeutic agent for the treatment of breast cancer. However, resistance to Doxo is common. Adjuvant compounds capable of modulating mechanisms involved in Doxo resistance may potentiate the effectiveness of the drug. Resveratrol (Rsv) has been tested as an adjuvant in mammary malignancies. However, the cellular and molecular mechanisms underlying the effects of cotreatment with Doxo and Rsv in breast cancer are poorly understood. Here, we combined in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 116 publications
(75 reference statements)
3
20
0
1
Order By: Relevance
“…In several studies, it has been proven that polyphenols can modulate the effects of doxorubicin and etoposide in neoplastic cells [ 28 , 29 , 30 , 31 , 32 , 33 ]. In general, they were found to intensify drug-induced apoptosis and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, it has been proven that polyphenols can modulate the effects of doxorubicin and etoposide in neoplastic cells [ 28 , 29 , 30 , 31 , 32 , 33 ]. In general, they were found to intensify drug-induced apoptosis and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, doxorubicin or etoposide in combination with polyphenols exert greater anti-tumor effects in the in vitro models [ 28 , 29 , 30 , 31 , 32 , 33 ]. In our previous study [ 34 ], we demonstrated that neobavaisoflavone (NBIF), a Psoralea corylifolia L. polyphenol, has a moderate effect on viability and growth in human U-87 MG glioblastoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol could inhibit the metastasis of liver cancer in vitro, which might be associated with up-regulating miR-186-5p. 肝癌是我国常见的消化系统恶性肿瘤之一, 居所有肿瘤发病率和病死率的第四位和第二位, 已成为严重威胁我国居民健康的一大疾病 [1] 。肝 细胞癌是肝癌最主要的组织学亚型,约占其总数 的 90% [2] 。尽管手术治疗、局部治疗和放化疗等 在肝癌中取得了一定的成效,但肝癌患者的 5 年 存活率仍不足 12% [3][4] 。肝癌患者的高病死率很 大程度上归因于患者在确诊时已发生转移。截 至目前,肝癌转移尚无有效的治疗方法 [5][6][7] 。因 此,临床上亟需开发可用于肝癌转移的新的治疗 药物。 白藜芦醇是一种非黄酮类多酚有机化合物, 最早从毛叶藜芦的根中分离得到,目前发现其存 在于藜芦、虎杖、葡萄等 70 多种植物中 [8] 。研究表 明,白藜芦醇具有抑制血小板聚集、保护心血管、 调节脂代谢、抗炎、抗氧化等多种生物学功能 [9] 。 近年研究发现,白藜芦醇对乳腺癌、结直肠癌、肝 癌等多种肿瘤的发生发展均具有抑制作用,是潜 在的辅助抗肿瘤化合物 [10][11][12] 。有研究报道,白藜 芦醇通过调控 EMT 相关蛋白表达抑制人乳腺癌细 胞 MDA-MB-231 的转移 [13] 。 已有多项研究报道,miRNA 可以调控 EMT,影 响肿瘤转移 [14][15][16] 。miRNA 是一类长度为 19~25 个 核苷酸的内源性单链非编码 RNA 分子,可与靶基 因mRNA 3′端结合负向调控基因表达 [17] 。Li 等 [18] 研究发现,miR-186-5p 在结肠癌细胞中表达下调, miR-186-5p 过表达可抑制肿瘤细胞 EMT 和转移; Shan 等 [19] 和 Lan 等 [20] 均报道 miR-186-5p…”
Section: Discussionunclassified
“…On the other hand, autophagy activation inhibits the pathway by degrading Dvl or β-catenin [ 107 , 108 , 109 ]. Opposed to BCSC cells, resveratrol could potentiate long-term apoptosis and senescence induced by acute treatment with doxorubicin but with cytoprotective autophagy activation to resist apoptosis, which was reversed upon inhibition of autophagy in MCF-7 cells [ 110 ]. Resveratrol treatment in cancer cells downregulated TP53-induced glycolysis and apoptosis regulator (TIGAR) expression, resulting in the subsequent reduction of glutathione, ROS accumulation, and activation of protective autophagy, wherein use of appropriate autophagy inhibitors induced cell death, suggesting combination therapy for cancer treatment [ 111 ].…”
Section: Roles Of Polyphenols In Autophagic Adaptation For Healthy Agingmentioning
confidence: 99%